2004
DOI: 10.1111/j.1440-1843.2003.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Airways obstruction in survivors of thoracoplasty: Reversibility is greater in non‐smokers

Abstract: Long-term survivors of TPL have an obstructive as well as a restrictive ventilatory defect. These patients have partial reversibility of the obstructive defect. The degree of reversibility found suggests that bronchodilator therapy may help these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, it is important to note that the M patients were mainly patients who experienced tuberculosis and therefore had an underlying intrinsic lung disease. [32][33][34][35] In the study of Jackson et al 6 patients who underwent a thoracoplasty had a 5-year survival rate of 64%, which is comparable to the survival of our M group.…”
Section: Article In Presssupporting
confidence: 67%
“…Furthermore, it is important to note that the M patients were mainly patients who experienced tuberculosis and therefore had an underlying intrinsic lung disease. [32][33][34][35] In the study of Jackson et al 6 patients who underwent a thoracoplasty had a 5-year survival rate of 64%, which is comparable to the survival of our M group.…”
Section: Article In Presssupporting
confidence: 67%
“…120 On the other hand, a more recent study comparing total respiratory system compliance in patients after thoracoplasty with tuberculous patients who had no surgery, concluded that thoracoplasty reduced compliance less than anticipated because of compensation by the contralateral hemidiaphragm. 127 Interestingly, although some authors found that the size difference of the two lungs was reflected in greater restriction after right than left thoracoplasty, 122 others could not see such difference. 123…”
Section: Pulmonary Functionmentioning
confidence: 99%